(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2025)
The purpose of this work is to analyze the pathological mechanisms, clinical manifestations, epidemiological trends, and long-term consequences of intra-uterine malnutrition (Intra-Uterine Growth Restriction — IUGR), with a focus on global and regional statistical data. This thesis also aims to highlight diagnostic approaches, preventive strategies, and the pharmacological and non-pharmacological interventions used to reduce perinatal morbidity and mortality associated with IUGR. With an emphasis on global and regional statistics and the implication for neonatal and life long health.